Tinjauan Estetika Bentuk Bangunan Masjid Agung Baitussalam Purwokerto - Dwi Candra Purnamasari; Ilham Abdul Malik (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
This study aims to examine the aesthetic review of the Baitussalam Great Mosque Purwokerto as a case study example in the context of religious architecture. The study was conducted to understand how aesthetic elements in mosque design contribute to the spiritual experience of the worshipers. This research method uses a descriptive qualitative approach by analyzing visual data and literature on mosque architecture and the concept of Islamic aesthetics. The results of the analysis show that the Great Mosque of Baitussalam Purwokerto incorporates a harmonization of traditional and modern elements in its design. The aesthetic beauty and the use of religious symbols create a calming atmosphere and provide a deep spiritual experience. This research can contribute to the development of an understanding of the importance of aesthetics in religious architecture and its application in the context of mosques in Indonesia.